SIG na gestão da água para a agricultura - Perdigão, António (Finisterra, 2003)
GIS IN WATER MANAGEMENT FOR AGRICULTURAL PURPOSES. The needs originating from the application of European Union’s CAP and Water Directive demand a very precise knowledge of the potential uses of water, especially in what concerns to its volumes, availability and quality. In Southern Europe this is particularly significant in order to conduct an eco-compatible management of water resources. Decision Support Systems (DSS) for agricultural purposes and management of agriculture vs. environment conflicts, assuming the need for a compatible water management, account for the objectives and tools adapted to the problems under analysis. The specificities of agricultural practices have been slowly requiring the use of information technology tools, monitoring and follow-up systems, GIS, simulation models and remote sensing approaches, using platforms with different spatial and temporal resolutions. Irrigation management involve availability of good quality data assuming that most information is dynamic, therefore requiring permanent updating (e.g. land use/land cover and climate data). However, the technical characteristics of the tools, very seldom are not adapted to the landscape units context or to the administrative/regional units, to which they are to be applied. The land units approach enables the thematic analysis of landscapes, assuming a strategy based on textures classified as spatial units, in terms of land use/land cover characteristics.